Older adults' views and experiences of doll therapy in residential care homes. (September 2015) - Alander, Heidi; Prescott, Tim; James, Ian A
Background and purpose: The mechanisms underlying the success of doll therapy are poorly understood. The aims of this study were to explore how people in care, doll users and non-users, make sense of doll use in their settings. Methodology: A grounded theory approach was used, recruiting participants from three residential care homes involving four male and 12 female residents. Data collection occurred in two phases; five participants took part in a focus group and later 11 participants were interviewed individually. Eight of the 11 participants had dementia, and four participants were actively using dolls. Results and conclusion: The results are presented as themes, and sub-themes, consisting of four main categories (intrapersonal features, interpersonal features, behavioural benefits, ethical and moderating factors). This thematic analysis shows that residents generally support the use of dolls, believing that dolls can have a positive impact on some users. The mechanisms by which this impact is achieved are discussed together with the ethical concerns.